Intervenções urbanas com Soluções Baseadas na Natureza e o Direito ao Lazer: Parque Linear Rachel de Queiroz em Fortaleza - Guerreiro, Ana Luiza Bezerra (2024)
The right to the city is the democratic access to urban space, which can be concisely understood as the geographic space that encompasses buildings, infrastructure, commercial activities, and areas for social and leisure purposes. Society interacts with urban space through a dialectical process. This research aims to evaluate the intervention of urban spaces through Nature-based Solutions (NbS) in the context of Brazil's Northeast region, with a focus on understanding how urban interventions impact the right to leisure for people with disabilities, those with reduced mobility, children, and the elderly. This analysis is significant due to the need for specific studies addressing the implementation of NbS in the urban spaces of the Northeast, taking into account distinct factors such as the relationship with urban waters, strategic planning, and the right to the city. To achieve this goal, the research adopts a case study method. The Rachel de Queiroz Linear Park in Fortaleza, Ceará, was selected as the object of study for several reasons, including its partial funding by an international agency — the International Bank for Reconstruction and Development (IBRD), its connection with Fortaleza's strategic planning, the completion of NbS implementation in its inaugurated sections, which allows for comparative analysis, and its location in the Northeast. The project analysis is based on two perspectives: the eight principles of walkability and behavioral mapping, providing a holistic approach. The findings address the research question: how can the implementation of Nature-based Solutions in urban spaces impact the right to leisure? The results indicate a positive impact on the use of these solutions in urban landscapes. The implementation of wetlands has contributed to integrating nature into urban daily life and advancing Sustainable Development, particularly regarding Sustainable Development Goal 11 — Sustainable Cities and Communities. This integration has made a densely populated area of the city with a history of socio-environmental challenges more attractive, promoting a space for leisure.